Role of financial intermediaries in capital market - KUMAR, DR. P. PRAVEEN; MS. G. SANTHYA, (The journal of contemporary issues in business and government, 2020)
This study tries to examine the role of financial intermediaries in capital market. And also looks over the impact of financial intermediaries on capital market development. Financial intermediaries exist for the profits within the Financial system. Capital market is the place where the savings and the investment have been done between the suppliers and the people who need the capital. The financial intermediaries arise to reduce the information of risk management and the mobilisation of the savings. These intermediaries assist the investors to grow their money by the way of investments. This paper comes to the opinion that financial intermediaries play a major part in the economy and helps the investors easily make investment in the capital market.